(untitled) (Baghdad Science Journal, 2004)
The derivatives formed after the successive acetylation, esterification and nitration reactions to cholic, deoxycholic, and taurocholic acids were identified to be of the following general strucure: Colt, Where RI=NO3, OH, 0=, or CH3COO. R2=H, NO3, OH, 0-=, or CH3COO. R3=H, NO3,01-1, 0=, or CH3COO. R4=OH, NH(CH2)2S03Na, NH(CH2)2S03H, or OMe. By using U.V-visible and I.R spectrophotometry . The number of hydroxyl groups was determined, purity was checked from T.L.C, Most of these derivatives will find pharmaceutical application.